TELAAH PERTIMBANGAN HAKIM MENJATUHKAN PUTUSAN BEBAS PERKARA PENCABULAN ANAK (Studi Putusan Nomor 104/Pid.Sus/2023/PN Tli.) - Elnajj Keysha Nabila; Bambang Santoso (Sebelas Maret University, 2025)
This article analyses criminal procedure law related to the suitability of the judge's consideration of rendering a judgment of acquittal of case of obscene act against a child in Verdict Number 104/Pid.Sus/2023/PN Tli. with the provision of Article 191 paragraph (1) of the Criminal Procedure Code. The purpose of this article is to determine whether the judge's consideration of rendering a judgment of acquittal of case of obscene act against a child in Verdict Number 104/Pid.Sus/2023/PN Tli. is in accordance with the provision of Article 191 paragraph (1) of the Criminal Procedure Code. This research is a normative or doctrinal legal research that is prescriptive and applied. Types of legal materials used are primary legal materials and secondary legal materials. The technique used in collecting legal materials is literature study or document study. The finding proves that the judge's consideration of rendering a judgment of acquittal of case of obscene act against a child in Verdict Number 104/Pid.Sus/2023/PN Tli. has been in accordance with the provision of Article 191 paragraph (1) of the Criminal Procedure Code.